2001
DOI: 10.1074/jbc.m100579200
|View full text |Cite
|
Sign up to set email alerts
|

Alanine-scanning Mutagenesis of Plasmatocyte Spreading Peptide Identifies Critical Residues for Biological Activity

Abstract: diminished activity to a lesser degree. The point mutants Y11A, T14A, T22A, and F23A had activity identical or only slightly reduced to that of wild-type PSP. The mutant PSP-(7-23) lacked the entire unstructured domain of PSP and was found to have no plasmatocyte spreading activity. Surprisingly, E1A and N2A had higher activity than wild-type PSP, but F3A had almost no activity. We thus concluded that the lack of activity for PSP-(7-23) was largely due to the critical importance of Phe 3 . To determine whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 25 publications
(41 reference statements)
2
35
0
Order By: Relevance
“…Binding Constants of Representative Peptides-Prior analysis indicated that several residues are invariant among ENF peptide family members (8,16). These include Cys 7 and Cys 19 , Thr 14 and Thr 22 , all of the charged amino acids in the structured C terminus (Arg 13 , Asp 16 , Arg 18 , and Lys 20 ), and the three N-terminal residues Glu 1 , Asn 2 , and Phe 3 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Binding Constants of Representative Peptides-Prior analysis indicated that several residues are invariant among ENF peptide family members (8,16). These include Cys 7 and Cys 19 , Thr 14 and Thr 22 , all of the charged amino acids in the structured C terminus (Arg 13 , Asp 16 , Arg 18 , and Lys 20 ), and the three N-terminal residues Glu 1 , Asn 2 , and Phe 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Peptide Synthesis and Purification-All peptides were synthesized on an Applied Biosystems 433 synthesizer using standard Fmoc chemistry as previously described (16,17). The resin-peptide was cleaved and deprotected for 4 h in reagent K (21), a mixture containing 5% phenol, 1.25% water, 2.5% thioanisole, and 2.5% dithioethane in trifluoroacetic acid.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations